2014
DOI: 10.1111/jpc.12692
|View full text |Cite
|
Sign up to set email alerts
|

Metered‐dose inhaler ipratropium bromide in moderate acute asthma in children: A single‐blinded randomised controlled trial

Abstract: In children with acute asthma of moderate severity who are treated with adequate doses of salbutamol and prednisolone, the addition of IB is not significantly associated with a reduction in admission rates. There is a significantly higher rate of adverse effects if IB is given. IB should be reserved for children with severe asthma exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Similarly, only a few studies have shown the effectiveness of IB‐MDI with a spacer for AAE in pediatric patients compared to a large body of evidence supporting treatments with nebulized IB. While an insufficient dosage of IB‐MDI might be the cause of these results, it was assumed that the drug delivery method was the main factor because 80 μg per dose of IB was administered to children aged 4 or 5 years and 160 μg per dose was administered to children aged ≥6 years both of which are considered to be adequate dosages according to the official guidelines of the Australian Asthama Handbook . Furthermore, although much research demonstrating the benefits of delivery via MDI with a spacer has recently been published worldwide, MDI use in the ED setting in Japan is still uncommon.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Similarly, only a few studies have shown the effectiveness of IB‐MDI with a spacer for AAE in pediatric patients compared to a large body of evidence supporting treatments with nebulized IB. While an insufficient dosage of IB‐MDI might be the cause of these results, it was assumed that the drug delivery method was the main factor because 80 μg per dose of IB was administered to children aged 4 or 5 years and 160 μg per dose was administered to children aged ≥6 years both of which are considered to be adequate dosages according to the official guidelines of the Australian Asthama Handbook . Furthermore, although much research demonstrating the benefits of delivery via MDI with a spacer has recently been published worldwide, MDI use in the ED setting in Japan is still uncommon.…”
Section: Discussionmentioning
confidence: 53%
“…While an insufficient dosage of IB-MDI might be the cause of these results, it was assumed that the drug delivery method was the main factor because 80 g per dose of IB was administered to children aged 4 or 5 years and 160 g per dose was administered to children aged 6 years both of which are considered to be adequate dosages according to the official guidelines of the Australian Asthama Handbook. 10,12 Furthermore, although much research demonstrating the benefits of delivery via MDI with a spacer has recently been published worldwide, MDI use in the ED setting in Japan is still uncommon. Thus, IB inhalation via MDI with a spacer is assumed to be less effective than nebulized IB in treating pediatric patients with asthma exacerbation and respiratory distress in the pediatric emergency care setting in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that switchers from Atrovent ® CFC MDI were more likely to be adults, have an indication of COPD and have moderate/severe disease. Due to the pathological differences between asthma and COPD alone, patients would experience different events, but additionally age and disease severity can also create different event profiles …”
Section: Discussionmentioning
confidence: 99%